(untitled) (Journal of Health, Population and Nutrition, 2009)
The global resurgence of interest in the social determinants of health provides an opportunity for determined action on unacceptable and unjust health inequalities that exist within and between countries. This paper reviews three categories of social inclusion policies: cash-transfers; free social services; and specific institutional arrangements for programme integration in six selected countries-Botswana, Mozambique, South Africa, Ethiopia, Nigeria, and Zimbabwe. The policies were appraised as part of the Social Exclusion Knowledge Network (SEKN) set up under the auspices of the World Health Organization’s Commission on Social Determinants of Health. The paper highlights the development landscape in sub-Saharan Africa and presents available indicators of the scale of inequity in the six countries. A summary of the policies appraised is presented, including whether or what the impact of these policies has been on health inequalities. Crosscutting benefits include poverty alleviation, notably among vulnerable children and youths, improved economic opportunities for disadvantaged households, reduction in access barriers to social services, and improved nutrition intake. The impact of these benefits, and hence the policies, on health status can only be inferred. Among the policies reviewed, weaknesses or constraints were in design and implementation. The policy design weaknesses include targeting criteria, their enforcement and latent costs, inadequate participation of the community and failure to take the cultural context into account. A major weakness of most policies was the lack of a monitoring and evaluation system, with clear indicators that incorporate system responsiveness. The policy implementation weaknesses include uneven regional implementation with rural areas worst affected; inadequate or poor administrative and implementation capacity; insufficient resources; problems of fraud and corruption; and lack of involvement of civil servants, exacerbating implementation capacity problems. The key messages to sub-Saharan African governments include: health inequalities must be measured; social policies must be carefully designed and effectively implemented addressing the constraints identified; monitoring and evaluation systems need improvement; and participation of the community needs to be encouraged through conducive and enabling environments. There is a need for a strong movement by civil society to address health inequalities and to hold governments accountable for improved health and reduced health inequalities. Key words: Health inequalities; Social Exclusion Knowledge Network; Social inclusion; Sub-Saharan Africa doi: 10.3329/jhpn.v27i4.3392 J Health Popul Nutr 2009 Aug;27(4):492-504